PENERAPAN RESTORATIVE JUSTICE DALAM PENCEGAHAN TERJADINYA LABELING TERHADAP ANAK PELAKU TINDAK PIDANA DI BANDAR LAMPUNG - Erna dewi (Balitbangda Provinsi Lampung, 2021)
The juvenile criminal justice process must prioritize the Restorative Justice approach, in Article 8 Paragraph (3) letter c of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System states that the Diversion process must pay attention to the avoidance of negative stigma or labeling. The problem in this research is the application of Restorative Justice in preventing the occurrence of labeling of children, as well as what are the inhibiting factors for the application of Restorative Justice. This research is a normative and empirical juridical research using primary and secondary data. The data collection method uses the interview method. Data analysis was carried out with qualitative literature. The results of research and discussion of facts in the field of Restorative Justice or Diversion are divided into two, namely Diversion not based on law and Diversion based on law. Restorative Justice can be used in preventing the occurrence of labeling of children to prevent children from formal justice processes and to return to the social environment. The inhibiting factor is the factor of the victim's family who wants the case to continue to be processed through the judiciary, the difficulty of being invited to a Diversion meeting as well as the mode of extortion against the perpetrator, the legal substance factor, legal structure, and legal culture. It is recommended that parents, families, and communities should guide and keep to watch the children so that they can grow according to the nature of the child and to anticipate the potential for criminal acts committed by children. The police should collaborate with related agencies to disseminate the importance of preventing labeling, especially for child perpetrators of criminal acts with Restorative Justice or Diversion among the community and always prioritizing Restorative Justice as an alternative to imprisonment so as to prevent labeling of children.